Ca(v)3.2 T-type calcium channel mutation influences kindling-induced thalamic neuronal firing patterns in Genetic Absence Epilepsy Rats From Strasbourg - (:unkn) unknown (WILEY, 2019)
Objective: Recent data indicate that amygdala kindling leads to significant changes in interictal neuronal firing patterns of thalamic reticular nucleus (TRN) neurons by decreasing the spontaneous firing rate and increasing burst firing in nonepileptic control (NEC) rats. Genetic Absence Epilepsy Rats From Strasbourg (GAERS) were resistant to these kindling-induced firing changes in TRN neurons, and are also resistant to the progression of kindling. We investigated whether a homozygous, missense, single nucleotide mutation (R1584P) in the Ca(v)3.2 T-type Ca2+ channel gene, which has been correlated with the expression of absence seizures in GAERS, influenced kindling progression and TRN firing patterns. Methods: Double-crossed (GAERS vs NEC; F2) rats that were homozygous for the Ca(v)3.2 mutation (PP) and those negative for the mutation (RR) were implanted with a stimulating electrode in the amygdala. Rats received a total of 30 kindling stimulations at their afterdischarge threshold current twice daily, and kindling progression was evaluated. Thereafter, the extracellular neuronal activity of TRN neurons was recorded in vivo under neuroleptanesthesia to investigate the influence of Ca(v)3.2 mutation on TRN firing patterns. Results: We found that the R1584P mutation did not affect kindling progression in F2 crosses (P = 0.78). However, it influenced kindling-induced neuronal firing of TRN neurons. After 30 stimulations, RR rats exhibited a lower firing rate and a higher percentage of burst firing compared to PP rats. The decrease in firing frequency was correlated with the increase in the amount of burst firing in RR rats (R-2 = 0.497). Significance: Our findings suggest that mutation in Ca(v)3.2 T-type Ca2+ channels may play a role in the resistance to kindling-induced changes in TRN neurons to a low-frequency and high-percentage bursting pattern seen in association with the convulsive stages of amygdala kindling, but is not in itself enough to explain the resistance to kindling progression observed in GAERS.
Keywords: amygdala kindling; Cav3.2 mutation; GAERS; thalamic reticular nucleus; ELECTRICAL-STIMULATION; SEIZURE EXPRESSION; MODEL; CACNA1H